Briquettes Of Activated Corncob Charcoal Burning Characteristics - Raharjo, Sapto; Lestari, Lina; Saleh, Ismail; Nyoman Sudiana, I; Dewi, Anita (Journal of World Science, 2023)
This study aims to find out and analyze the characteristics of briquettes in burning activated corn charcoal. The preparation procedure of this study includes material collection, carbonization, crushing, sifting through an 80-mesh sieve, activation, merging with adhesives, compaction, and drying. Sago powder is used as an adhesive with a mass ratio of 9:1. After being heated separately at 550°C and 650°C for 30 minutes and 20 minutes, the samples were compressed at various pressures. Another difference in compaction pressure also leads to similar results. Untreated corn cob briquettes reach their maximum temperature before activated corn cob briquettes. At an activation value of 550°C for 30 minutes and a compaction pressure of 70.33 kg/cm2, the highest combustion temperature was 528°C. In this study, it can be identified characteristics that can improve the burning efficiency of corn charcoal. This research has implications for better combustion efficiency, can reveal factors that affect combustion efficiency.